2008
DOI: 10.1200/jco.2007.12.0410
|View full text |Cite
|
Sign up to set email alerts
|

Five-Gene Model to Predict Survival in Mantle-Cell Lymphoma Using Frozen or Formalin-Fixed, Paraffin-Embedded Tissue

Abstract: We here present a validated qRT-PCR-based test for survival prediction in patients with MCL that is applicable to fresh frozen as well as to FFPE tissue specimens. This test may prove useful to guide individualized treatment approaches for patients with MCL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(62 citation statements)
references
References 51 publications
1
61
0
Order By: Relevance
“…In addition to the translocation and overexpression of cyclin D1, a number of other genetic and nongenetic alterations resulting in deregulated cell cycle progression and/or reduced apoptosis have been reported in MCLs. 1,10,11,40,43,44,48,49 In that line, pharmacological inhibitors of Wnt signaling or knockdown of components of the pathway reduce proliferation and trigger apoptosis in MCL cells. 5,6 Our data show that ZEB1 could have a role in the regulation of proliferation and apoptosis in MCL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the translocation and overexpression of cyclin D1, a number of other genetic and nongenetic alterations resulting in deregulated cell cycle progression and/or reduced apoptosis have been reported in MCLs. 1,10,11,40,43,44,48,49 In that line, pharmacological inhibitors of Wnt signaling or knockdown of components of the pathway reduce proliferation and trigger apoptosis in MCL cells. 5,6 Our data show that ZEB1 could have a role in the regulation of proliferation and apoptosis in MCL.…”
Section: Discussionmentioning
confidence: 99%
“…40,48,49 In addition to Ki-67, traditionally used in clinical applications, 48 gene and protein expression analyses in primary MCLs have identified different markers associated to proliferation that independently or jointly serve as predictors of worse prognosis in MCL. 40,48,49 We therefore explored The EMT activator ZEB1 in MCL E Sánchez-Tilló et al whether ZEB1 expression associates to proliferationassociated genes. Indeed, ZEB1 was positively correlated with the proliferation signature average defined by Rosenwald et al 40 , a number of genes included in that signature (HMGB2, UHRF1, and CENPF), as well as well-known proliferationrelated genes like MYC and MKI67 (Supplementary Table S1).…”
Section: H-thymidine and Brdu Incorporation (Figures 4b And C)mentioning
confidence: 99%
“…However, a microarray-based technique is not feasible on a wide scale. Therefore, further testing of a minimum number of genes by formalin-fixed, paraffin-embedded tissue specimens has been studied [24]. This study identified five genes including RAN, MYC, TNFRSF10B, POLE2, and SLC29A2 which were …”
Section: Risk Stratificationmentioning
confidence: 99%
“…The majority of genes associated with outcome in MCL are expressed in a proliferation-dependent manner (27). This proliferation signature was later used as a basis for the development of a quantitative PCR assay successfully applied to FFPE tissue (57). Another 26-gene expression signature also showed prognostic significance, but, similar to the PCR-based assay, incorporated additional proliferation-independent genes (42).…”
Section: Gene Expression Profilingmentioning
confidence: 99%